Cooking banana marketing protocol (English). - Kikulwe, Enoch Mutebi (2016)
This protocol is designed to support farmers to improve the quality of their bananas in the field and the postharvest practices in a bid to facilitate access to better prices and niche markets. The protocol is organized into three sections: Section 1 Good Agricultural Practices (GAP); Section 2: Proper Harvest and Handling Practices and Section 3: Good Marketing Practices (GMP).